Analisis Faktor Penghambat Pembelajaran Bola Voli Mini pada Siswa Kelas IV dan V Sekolah Dasar - A. Jalil; Winda Nuraisyah; Mas’odi (MAN Insan Cendekia Jambi, 2026)
This study aims to identify and analyze the inhibiting factors of fourth and fifth grade students in learning mini volleyball at SDIT Pangarangan Sumenep. The study used a quantitative approach with a descriptive design. The research subjects were 51 students who were determined through a total sampling technique. Data were collected using a closed questionnaire that had undergone content validity and reliability tests with a Cronbach's Alpha coefficient of 0.872. The instrument included internal factors (psychological and physical) as well as external factors (social, environmental, and cultural). Data were analyzed using descriptive statistics with a percentage technique. The results showed that the dominant obstacles were found in internal factors, especially physical (59%) and psychological (51%) indicators. In external factors, social indicators showed obstacles of 57%, while environmental indicators were relatively lower (45%). These findings indicate that learning obstacles are multidimensional and influenced by the interaction of individual student readiness and learning environment support. This study provides practical implications for physical education teachers to modify learning tools and approaches that are more adaptive in order to improve the effectiveness of mini volleyball learning in elementary schools.